A new carbazole-based colormetric and ratiometric fluorescent probe for hypochlorite sensing in living cells and zebrafishes. (September 2020) - Feng, Aiqing; Liu, Peilian; Liang, Qiqi; Zhang, Xinyi; Huang, Liping; Jia, Yongmei; Xie, Mubiao; Yan, Qing; Li, Chengpeng; Wang, Sheng
Abstract: In this work, we have developed a new carbazole-based fluorescent probe ( E )-1-methyl-4-(2-(5-(9-phenyl-9 H -carbazol-3-yl) thiophen-2-yl)vinyl)pyridin-1-ium (PCTP ) for ratiometric and colormetric ClO − sensing. PCTP displayed red emission due to the intramolecular charge transfer (ICT) effect of phenylcarbazol moiety, while this effect can be rapidly weakened and led to the significant fluorescence change (from red to green) in the presence of ClO − . PCTP is more highly selective and sensitive towards ClO − detection than other various biological related species. The detection limit (LOD) was calculated to be 10.8 nM. More importantly, PCTP has been successfully applied in ClO − imaging in living cells and zebrafishes. Highlights: A novel colormetric and ratiometric fluorescent probe (PCTP ) was designed and synthesized for detecting ClO − . PCTP displays a low detection limit (10.8 nM) and large Stokes shift (124 nm). PCTP successfully performed well in sensing ClO − in living cells and zebrafishes.